An Analysis of the Students’ Speaking Ability Through Storytelling at the Eighth Grade of UPTD SMP Negeri 3 Gunungsitoli in 2021/2022 - Kristof Martin Efori Telaumbanua (Journal on Education, 2024)
In the Syllabus for class VIII UPTD SMP Negeri 3 Gunungsitoli, the MCC, especially for class VIII, is 70, which students must achieve in order to be successful in English lessons. The aims of this research are 1) To analyze students' speaking abilities through storytelling and 2) To analyze the factors that influence students' speaking abilities through storytelling. Therefore, this research was conducted to find out the answer. Furthermore, the research informants were 15 students in class VIII-A UPTD SMP Negeri 3 Gunungsitoli. After analyzing student tests and interviews, the researchers concluded that class VIII-A students at UPTD SMP Negeri 3 Gunungsitoli had level 3+ (good level) with the highest percentage of ability (89.6%) in this field. speak through telling personal experiences. The percentage levels are followed by level 3 (36.6%), level 4 (36.6) and level 2+ (12.6). Apart from that, research findings also reveal that factors that influence students' ability to speak through personal experience of telling stories are the frequency of practice and repetition of topics, the type of speaking material and teaching and learning methods/approaches. Finally, the researcher wrote several suggestions: For English teachers, it is important to improve the way they teach English, especially in conveying speaking material to students. The frequency of practice must be increased, various topics such as storytelling, especially about personal experiences, the use of English needs to be given to students in every material studied so that they can train students' self-confidence, students' obstacles in speaking practice can be overcome one by one. As future researchers, it is hoped that they will be able to conduct better research on this research topic in the future.